Analisis Faktor Adaptasi Instrumen Resiliensi Akademik Versi Indonesia: Pendekatan Eksploratori dan Konfirmatori: Factor Analysis on The Academic Resilience Scale (Indonesian Version): The Utilization of EFA and CFA approaches - Dewi Kumalasari; Luthfiyanni, Noor Azmi; Grasiaswaty, Novika (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
Academic resilience is an individual response to overcome the academic difficulties. Scholars indicate that academic resilience has three dimensions,1)Perseverance, which reflects behavioral responses, 2) Reflection,and 3) Adaptive help-seeking, which reflects cognitive responses and negative affect and emotional responses that reflect the affective dimension. The Academic Resilience Scale (ARS-30) is the latest instrument that measures academic resilience. Unfortunately, the scale has not been adapted inthe Indonesian version.An adaptation process is needed to suit with the Indonesian’s context and culture. Theaimof this study wasinvestigatingthe validationofthe ARS-30in the Indonesian version. Adaptation process wascarried out following guidelines by the International Test Commission(ITC). Data were collected from 586 college student in Indonesia selected from accidental sampling. Based on the analysis of reliability testing, Exploratory Factor Analysis (EFA)and Confirmatory Factor Analysis (CFA)using JASP indicatedthat the ARS-Indonesiaversionwasvalid and reliable to measureacademic resilience. Discussion and implication of theARS-Indonesia model were presented in the following article.